Captopril-Associated Cough Is Not due to Increased Airway Responsiveness - SP Blackie; C Hilliam; R Porter; R Rangno; PD Paré (Canadian Respiratory Journal)
BACKGROUND: Angiotensin-converting enzyme (ACE) inhibitors commonly cause cough. There is controversy as to whether preexisting airway hyperresponsivencss predisposes patients to ACE inhibitor-induced cough and whether ACE inhibitor therapy can cause airway hypcrresponsiveness.